The Effect of Aminopterin Sodium on Plasma Fibrinogen, Antifibrinolysin and Euglobulin Lysis Time - Johnson, J Frederic; Zeineh, Rashid A (Thrombosis and Haemostasis, 1963)
The daily oral administration of Aminopterin Sodium to normal dogs was accompanied by an increase in plasma antifibrinolysin concentration, an increase in plasma fibrinogen concentration and a decrease in euglobulin fibrinolytic activity.